2017
DOI: 10.1136/postgradmedj-2017-135212
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of interventions to foster physician resilience

Abstract: This review aimed to synthesise the literature describing interventions to improve resilience among physicians, to evaluate the quality of this research and to outline the type and efficacy of interventions implemented. Searches were conducted in April 2017 using five electronic databases. Reference lists of included studies and existing review papers were screened. English language, peer-reviewed studies evaluating interventions to improve physician resilience were included. Data were extracted on setting, de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
93
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(110 citation statements)
references
References 92 publications
5
93
0
6
Order By: Relevance
“…40 A systematic review of 22 low to moderate quality studies identified that psychosocial skills training and mindfulness training may be promising strategies to build resilience in physicians. 41 Our survey has several strengths. First, it is the first national, cross-sectional, survey focused on career satisfaction, overall and by gender.…”
Section: Discussionmentioning
confidence: 99%
“…40 A systematic review of 22 low to moderate quality studies identified that psychosocial skills training and mindfulness training may be promising strategies to build resilience in physicians. 41 Our survey has several strengths. First, it is the first national, cross-sectional, survey focused on career satisfaction, overall and by gender.…”
Section: Discussionmentioning
confidence: 99%
“…Many of the elements of resilience emerging from these data have been described in other populations, including the importance of positive attitude, social supports and physical activity. Some elements that are common in other resilient individuals, such as a strong spiritual base, were largely absent from this cohort . The novel framework for how these forces influence resilience bears resemblance to social ecological models of human development.…”
Section: Discussionmentioning
confidence: 99%
“…The phenomenon of resilience has not been well studied among physicians. A recent review of interventions to increase resilience demonstrated heterogeneous methods and measurements, which the authors conclude is a result of a lack of clarity around the concept …”
Section: Introductionmentioning
confidence: 99%
“…Educators have explored a number of techniques for developing adaptability and resilience in health care students and practitioners. [28][29][30][31] Researchers have found evidence that a variety of approaches may be useful in developing adaptability and resilience in both students and practicing professionals. 29 The research findings revealed that the most promising approach may be a combination of strategies including components such as (1) education about resilience, (2) creative problem-solving opportunities, (3) mentoring, (4) psychosocial and mindfulness skill training, and (5) exposure to challenging and unpredictable practice situations.…”
Section: Adaptability and Resilience Developmentmentioning
confidence: 99%